Systematics, biology and ecology of New Zealand's pygmy mistletoes (Korthalsella: Viscaceae) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Ecology at Massey University, Manawatu, New Zealand - Sultan, Amir (Massey University, 2014)
New Zealand’s pygmy mistletoes belong to the genus Korthalsella Tieghem, which comprises about 30 species ranging from Malesia to Hawaii, the Marquesas and Henderson Islands in the east, Japan in the north, Australia, New Zealand in the south, and Ethiopia and Madagascar to the west. Mainland Australia, Hawaii, Malesia and Madagascar all have high levels of species richness. This thesis shows that Korthalsella has high levels of regional endemism and has widespread parallelism and supports the biogeographic model of speciation, whereas, the traditional sections based on morphology are not supported. Korthalsella is represented in New Zealand by a monophyletic clade of three species K. clavata (Kirk) Cheeseman, K. lindsayi (Oliver ex J. D. Hooker) Engl., and K. salicornioides (A. Cunningham) Tiegh. Korthalsella clavata and K. lindsayi are both generalists with relatively broad host ranges whereas K. salicornioides is a specialist species with most host records from two myrtaceous genera Kunzea Rchb. (kanuka) and Leptospermum J. R. Forst & G. Forst (manuka). Cross-infection experiments in Korthalsella salicornioides indicate the presence of putative Kunzea- and Leptospermum-specific races with better success rates of seedling survival when maternal and recipient hosts were the same. However, genetic data based on nuclear internal transcribed spacer (ITS) and chloroplast trnQ-rps16 spacer sequences does not support the presence of host related variability and the within-species genetic structure appears to be geographic rather than host-based. My study shows that both cpDNA haplotypes and ITS sequence types are shared between K. clavata and K. lindsayi, which possiby is an outcome of hybridisation and introgression between the two species. Korthalsella salicornioides is an ambophilous species relying both on insects and on wind for effective pollination, whereas K. lindsayi is an anemophilous species. This study confirms the presence of explosive seed discharge in both species with dispersal distances ranging up to 4 and 7 m in K. lindsayi and K. salicornioides, respectively. However, dispersal distances of around 1 m are more typical. This study also describes the first account of clonal propagation by means of proliferation of endophyte and formation of adventitious sprouts in these species. Several new natural enemies specialising on New Zealand Korthalsella were discovered - two specialist armoured scales (Leucaspis albotecta Henderson and L. trilobata Henderson), a felt scale (Eriococcus korthalsellae Henderson), and two pathogenic ascomycetes Guignardia korthalsellae Sultan, Johnston, Park & Robertson and Rosenscheldiella korthalsellae Sultan, Johnston, Park & Robertson. Other natural enemies include a specialist gall mite Aceria korelli Manson, whereas generalists include native and adventive scale insects and generalist Lepidoptera. Demographic study of several populations revealed that all species have high growth rates and high ramet turnover. Korthalsella salicornioides and K. clavata had relatively stable recruitment rates in all size/stage classes whereas K. lindsayi populations were apparently declining at the two study sites.
Keywords: New Zealand mistletoes; Mistletoe ecology; Pygmy mistletoe; Korthalsella; Korthalsella clavata; Korthalsella indsayi; Korthalsella salicornioides